Pengaruh Chest Physiotherapy Terhadap Penurunan Frekuensi Batuk Pada Balita Dengan Bronkitis Akut Di Balai Besar Kesehatan Paru Masyarakat Surakarta - Fitriananda, Eva; Edy Waspada, Edy Waspada.,SSt.FT., S.Fis., M.Kes (2017)
Background: Acute bronchitis is one of respiratory tract infections are the most common and occur for two weeks to three weeks. Acute bronchitis is most often strikes children under 5 years old. The main cause in cases of acute bronchitis was 95% due to a virus infection and 5% due to bacterial infection. Signs and symptoms that occur in acute bronchitis is a cough and have a cold. Based on these problems, physiotherapy as health workers played a role in handling cases of acute bronchitis with the aim to restore lung function and reduce the problems that exist. This study uses the author of chest physiotherapy modalities in the form of postural drainage, tappotement and vibration. Chest physiotherapy is a very effective way of physiotherapy in an attempt to remove secretions and improve ventilation in patients with impaired lung function. Objective: Knowing the effect of chest physiotherapy to decrease the frequency of cough in infants with acute bronchitis. Methods : Kind of research was Quasi Experimental. The study design used "pre-post test with control group design". In the design of this research there are two groups: the treatment group and the control group. Respondents from the study of 20 people, with 10 people in treatment group and 10 as control group. Cough frequency measurements conducted by Cough frequency questionnaire. Results : From the statistical test result with Paired T Test get significant value of p <0.05 (p = 0.012) and the influence of different test data between the control group and the treatment group using Independent T Test showed significant with p <0.05 (p = 0.0001). Conclusion : There is effect of giving chest physiotherapy to decrease the frequency of cough in children with acute bronchitis, and there is the difference between the control group and the treatment of chest physiotherapy treatment to decrease the frequency of cough in infants with acute bronchitis. Keywords : Chest Physiotherapy, Cough Frequency and Acute Bronchitis.